Effects of ultrathin igneous sill intrusion on the petrology, pore structure and ad/desorption properties of high volatile bituminous coal: Implications for the coal and gas outburst prevention. (15th May 2022) - Qin, Yujin; Jin, Kan; Tian, Fuchao; Su, Weiwei; Ren, Shaokui
Highlights: Effects of ultrathin (thickness ≈ 1 m) igneous sill intrusion on high volatile bituminous coal were comprehensively investigated. Differences between the ultrathin and ordinary igneous intrusion on coal's properties were compared. How to use the changing trend of thermal affected coal's physical and gas desorption characteristics as signs for the hard-detectable small igneous intrusion as well as outburst risk were discussed. Abstract: As the one of the most catastrophic mining hazards, coal and gas outburst seriously threatens the mining safety of collieries. Previous studies indicate that lots of outbursts are closely related to igneous intrusion. Thus, to further understand the influence of igneous intrusion on coal's physical properties and outburst risk (especially the impacts from ultrathin igneous sill intrusion, which is hard to be detected underground), the combined analyses of petrographic, proximate, pore structure and methane ad/desorption are applied. Results indicate that with the approaching to the ultrathin igneous sill, physical properties of coal change significantly. Due to thermal evolution effect from intrusion, metamorphic grade of coal increases from the high volatile bituminous coal (Ro = 0.6949) of unaffected normal region to the low volatile bituminous coal (Ro = 1.6684), and the altered range of thermal evolution zone is larger than 3 times of the sill thickness but of which the range of strong thermal evolution zone only reaches 0.8 times of the sill thickness. Within the thermal evolution zone: moisture content of coal decrease while the ash content increase when approaching to the sill; micropore volume and specific surface area of the coal are nearly unchanged in the weak thermal evolution zone but reduced in the strong thermal evolution zone, however, methane adsorption capacities of the coal are generally enhanced when comparing to the normal region sample; the transition pores and mesopores pore of the sample close to distal boundary of thermal evolution zone is seriously suppressed (which are 49.21–68.32 % and 20.14–63.31 % of the normal sample, respectively). By comprehensively considering the impact of igneous intrusion on coal, coal locates near the distal boundary of strong thermal evolution zone (about 0.5 times of sill thickness away from the intrusion boundary) seems to have the most serious threat of outburst risk. Additionally, the moisture, ash contents and the gas desorption property of coal has the feasibility to be used as the signs for the hard-detectable small-scale igneous intrusion ahead during roadway tunneling process. Meanwhile, due to the correlation between igneous intrusion and outburst, which can also be regarded as the early warning indicator for outburst prevention.